Intestinal absorption of colostral leukocytes, peripheral blood mononuclear cells, and porcine umbilical cord matrix stem cells by neonatal pigs - Miller, Danielle (Kansas State University, 2008)
Intestinal absorption of colostral leukocytes (CL), peripheral blood mononuclear cells (PBMC), and porcine umbilical cord matrix stem cells (PUC) was analyzed in neonatal pigs. Maternal CL have previously been demonstrated in pigs, and maternal PBMC have been observed in calves to enter neonatal circulation after ingestion. PUC are primitive stem cells that are easily isolated from Wharton's jelly of the porcine umbilical cord. These cells do not have an immunogenic effect on the host upon initial transplantation. The general characteristics of PUC may allow them to serve as a delivery system to the neonate. Cellular migration through the duodenum, jejunum, and ileum was assessed using confocal microscopy. In vitro experiments utilized an organ explant culture system to determine the trafficking of labeled cells. Small-intestine tissue was collected from stillborn and sacrificed neonates. All three cell types (CL, PBMC, and PUC) were detected below the luminal surface, after 72 h of culture with media, and regardless of whether explants were from stillborns or live-born pigs. In vivo trafficking was assessed using neonatal pigs that were fed PBMC isolated from their mother or PUC from an unrelated pig. The effect of prior exposure to 25% acellular colostrum (AC) in medium was evaluated for both cell types. Piglets were euthanized 8 h or 24 h post feeding and sections of the small intestine collected. Both PBMC and PUC were found in all intestinal samples. Exposure to AC had no detected effect on the ability of either cell type to attach and migrate into the tissue. Labeled PUC were detected on the surface of the epithelium and in the lamina propria 8 h post treatment. PBMC were observed on the surface of the epithelium, in the lamina propria, and superficial submucosa 8 h following ingestion. In neonates sacrificed 24 h post treatment, both PUC and PBMC were observed on the surface of the epithelium, in the lamina propria, superficial submucosa, and deep submucosa of the small intestine. PUC and PBMC were noted at the apex, intermediate between the apex and the base, or at the base of the villus.
Keywords: Intestinal absorption; Colostrum; Pig umbilical cord matrix stem cells; Neonatal pig; Peripheral blood mononuclear cells; Colostral leukocytes; Agriculture, Animal Pathology (0476); Biology, Animal Physiology (0433)